SUPERVISI KLINIS OLEH KEPALA SEKOLAH TERHADAP KUALITAS PEMBELAJARAN - Kartini, Kartini; Susanti, Susanti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
This study uses a descriptive method with a qualitative approach. Data collection techniques are used through observation, interviews, and documentation studies. The research subjects were principals, vice principals, teachers, and school supervisors at Rimau Island 3 Public Middle School. The results of the study show that: (1) the Head of Rimau 3 Public Middle School has the ability to carry out good supervision, including in preparing academic supervision and clinical supervision programs for teachers. This can be seen from the supervision program that has been prepared by setting the goals, objectives, and procedures for implementing supervision and already cooperating with the school supervisor. (2) The Head of Rimau 3 Public Middle School has shown good supervision, especially in implementing an academic supervision and clinical supervision program. This can be seen from the application of the model, approach, and supervision techniques carried out by the principal, but in the application of observation techniques are equipped with observation guidelines and (3) Supervisory ability of the head of Rimau 3 Public Middle School, especially in providing follow-up supervision results is still lacking. This can be done from the follow-up of supervision results by evaluating and providing feedback through individual talks with supervised teachers, but the principal has not yet developed an action plan for the next supervision.